Design and experiment of a Chinese chive harvester - Feng, Yulong; Yin, Xuchao; Jin, Hairong; Tong, Wenyu; Ning, Xiaofeng (International Journal of Agricultural and Biological Engineering, 2023)
Recognizing the labor intensity of current domestic Chinese chive harvesting and the need for its mechanized harvesting, a self-propelled electric Chinese chive harvester is designed. The machine is composed of a control system, supporting mechanism, cutting parts, conveying and clamping mechanisms, frame, and collection system. It can complete Chinese chive feeding, cutting, transmission, and binning operations at one time. It has a cutting width of 0.25 m and wheelbases of 260 mm and 460 mm. Two 12 V, 42 Ah lead-acid batteries were used in series as the power supply. The mechanical properties of Chinese chive were analyzed, and shear and compression tests were carried out to determine that the average value of the maximum shear force on the chives is 129 N. Up to a compressive force of 225 N, Chinese chives are not damaged. According to the physical characteristics of Chinese chives and the requirements of the harvesting operations, design and calculation of the key components of the harvester's transmission mechanism and the strength of the whole machine frame were completed. An embedded control system and Cortex-M3 microprocessor were used to control the harvester and realize its functions of rolling and harvesting while regulating its speed and protecting its motor. Using the Box-Behnken test design method, the machine's operating speed, cutter speed, and cutter height were selected as influencing factors, and the lodging rate and loss rate were evaluated as a test. A mathematical regression model of influencing factors and evaluation indexes was established to analyze the influence of these factors and indexes and optimize test parameters. The optimal parameter combination is determined to be: operating speed, 1.1 km/h; cutter speed, 220 r/min; cutter height 2.0 cm. The parameters were verified from field tests and the results showed that under the optimized parameter combination, the average lodging rate was 3.96% and the average loss rate was 3.23%, indicating that the Chinese chive harvester meets the agronomic requirements of Chinese chive harvesting. This harvester could be modified to harvest other crops such as chrysanthemums and Mongolian Chinese chive.Keywords: harvester, clamping mechanism, test design, lodging rate, Chinese chiveDOI: 10.25165/j.ijabe.20231602.7067Citation: Feng Y L, Yin X C, Jin H R, Tong W Y, Ning X F. Design and experiment of a Chinese chive harvester. Int J Agric & Biol Eng, 2023; 16(2): 125-131.